2011
DOI: 10.1590/s0103-84782011005000128
|View full text |Cite
|
Sign up to set email alerts
|

Aerobiologia de Cercospora kikuchii

Abstract: II Aerobiologia de Cercospora kikuchii Aerobiology of Cercospora kikuchii RESUMO Neste estudo, foram quantificados os conídios de

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 12 publications
2
2
0
5
Order By: Relevance
“…Kudo et al (2011), showed that a 72-h wet period after C. sojina inoculation was sufficient to generate enough disease intensity for soybean genotype screening, a result that closely resembled those by Scandiani et al (2010). Under these conditions, we observed the first symptoms on the eighth day after inoculation.…”
Section: °Csupporting
confidence: 73%
“…Kudo et al (2011), showed that a 72-h wet period after C. sojina inoculation was sufficient to generate enough disease intensity for soybean genotype screening, a result that closely resembled those by Scandiani et al (2010). Under these conditions, we observed the first symptoms on the eighth day after inoculation.…”
Section: °Csupporting
confidence: 73%
“…Diseases are closely linked to climatic conditions, that is, temperature and humidity. Endof-cycle diseases manifest themselves with greater intensity when the temperature varies between 20 and 30 ºC and when the rains are frequent and above normal (KUDO et al, 2011). In the present experiment, favorable climatic conditions occurred for the occurrence of CLSD (Table 1).…”
Section: Resultssupporting
confidence: 46%
“…Wet weather during the growing season favors the development of the disease. RH above 80% and tem perature from 20°C to 24°C are more favorable for the germination of conidia and disease develop ment (Kudo et al 2011). The fungus overwinters in diseased crop residue as well as on infested seed.…”
Section: Purple Seed Stainmentioning
confidence: 99%